APLIKASI KEHADIRAN SISWA BERBASIS ANDROID MENGGUNAKAN QR CODE DI BIMBEL EXCELLENT INSTITUTE - Darul Mukminin; Ameliana Ameliana; Adiiba Dwikanthi; Lukas Umbu Zogara (Universitas Teknokrat Indonesia, 2022)
Excellent Institute (EXIST) is one of the private tutoring institutions engaged in education. This institution is a place for final-level students to get a debriefing to learn various lessons. Currently the agency still uses a manual attendance system. Each student needs to sign the attendance sheet provided by the teacher. If the final-level student attendance score each month is above 79%, then students will follow try out and in the next month students will settle in the same class and have benefits. The benefit obtained by students is to get new material after the try out. But if the student attendance score is below 80%, the student cannot take the try out and the student is transferred to the class by getting the material before the try out. This presence system generated by Rivest Code 4 (RC4) to performs QR Code scanning. The RC4 algorithm is one type of code that can be operated its encryption value that is performed per character 1 byte in one operation used by symmetrical keys in the form of chipper streams. The result of this study is to create an attendance application to make it easier for teachers and students to perform attendance.